Agroecosystems with greater canopy cover increase soil organic carbon density and reduce soil erodibility in the Peruvian Amazon - Chuchon Remon, Rodolfo Juan (2026)
Introduction: Soil degradation in tropical agricultural landscapes represents one of the major challenges for sustainability and food security, particularly in the Peruvian Amazon. In this region, the loss of vegetative cover alters carbon storage and increases vulnerability to erosion. This study evaluated how gradients of canopy structure in representative agroecosystems—cassava with no canopy (CV-S), oil palm with intermediate canopy density (OP-S), cacao with medium-density canopy (CC-S), and coffee with high-density canopy (CF-S)—influence soil organic carbon density (SOCD) and erodibility (K factor). Methods: A total of 1,049 soil samples (0–20 cm) were collected across three Amazonian regions and analyzed for their physical, chemical, and textural properties, complemented by multivariate and geostatistical analyses using ordinary kriging. Results: Results showed that SOCD increased consistently with canopy density, from 32.68 t C ha⁻¹ in CV-S to 82.64 t C ha⁻¹ in CF-S. The Factor K exhibited the opposite pattern, decreasing from 0.31 to 0.16 as tree cover increased, indicating greater resistance to erosion. Erodibility was primarily determined by soil texture, with a strong positive correlation associated to silt content (r = 0.89) and a negative with sand content (r = –0.74). Likewise, SOCD showed a very high correlation with total nitrogen (r = 0.96), reflecting a tight coupling between carbon accumulation and nutrient availability under denser canopies. Principal component analysis further revealed that dense-canopy systems are related to higher SOCD and total nitrogen, whereas canopy-free systems are linked to higher bulk density and greater susceptibility to erosion. Discussion: Spatial modeling showed that agroecosystems with more developed canopies exhibit better spatial structure and predictive performance, indicating a more stable edaphic organization under dense tree cover. Taken together, the results demonstrate that canopy structure functions as a key ecological regulator in Amazonian agroecosystems, with higher canopy cover promoting greater soil carbon accumulation while reducing soil erodibility. This highlights that dense-canopy systems, such as coffee and cacao, represent effective strategies to strengthen the sustainability and resilience of agricultural landscapes in the Peruvian Amazon.